Impact of Covid-19 Pandemic on Higher Education Sector in Yemen and Response Requirements - Khalil Mohammed Al Khateeb; Ali Abdullah Al Awadhi (مجلة الدراسات الاجتماعية, 2021)
This study aimed at identifying the impact of Covid-19 pandemic on higher education sector in Yemen and the requirements of fighting the consequences. To achieve this objective, the study followed the descriptive content analysis method. The population and sample of the study were (46) items selected from the literature. Major findings revealed consequences of Covid-19 included suspension of university study, death of some university staff, spread of fear and anxiety among academic community, administrative staff and students, inability of Yemeni universities to use an alternative e-learning system (due to the lack of institutional technology), lack of e-learning material, bad internet services and the spread of technological illiteracy among most of teaching staff and students. In light of these findings, the study is concluded with a set of recommendations as follows: the creation of a unified body under the supervision of the two parties in Sana'a and Aden to manage Covid-19 crisis; strengthening awareness of protection; supporting medical services; providing the staff of the Ministry of Higher Education with health insurance; building technological capacity of universities to overcome technology illiteracy; and developing e-learning.